Imaging Characteristics of Abdominal Aortic Aneurysm on CTscanner at E Hospital - Son, Nguyen Van; Phuong Anh, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 3, 2023)
An abdominal aortic aneurysm is a swelling (aneurysm) of the aorta. Abdominal aortic aneurysms often grow slowly without noticeable symptoms. Therefore, screening by clinical examination combined with imaging methods to detect disease early helps to reduce morbidity and mortality. Computed tomography (CT) is becoming increasingly common and is a good method for detecting abdominal aortic aneurysms. This study aims to describe the imaging characteristics of aortic aneurysms on computed tomography scans at E Hospital. This study was conducted on 34 patients with abdominal aortic aneurysm on CTscanner at E Hospital from June 2022 to May 2023 by a retrospective combined prospective method. The results indicated that patients over 60 accounted for 94.1%. Male: 61.8%, female: 38.2%. Aneurysm of under renal artery: 100%. Lozenge aneurysm: 97.1%, bag shape aneurysm: 2.9%. Calcify of vessel wall: 61.8%. Thrombosis of vessel wall: 58.8%. Diameter of aneurysm ≤ 50 mm: 82.4%. Length of aneurysm ≤ 50 mm: 61.8%. Injury of lateral artery: 35.3%. Of these, iliac artery: 41.7%. Conclusion: Computed tomography helps to identify and evaluate the characteristics of the aneurysm, thereby contributing an important part to making treatment methods for patients.